EU development cooperation: From model to symbol - Arts, Karin (Manchester University Press, 2004)
It is increasingly recognised that EU development cooperation policy has failed to meet its stated aims. In this book Arts and Dickson ask the obvious and important question: if the policy doesn't work, why bother with it? The authors assess why EU development policy has become largely ineffective, citing among the external causal factors the liberalisation of trade, and the growing influence of US and international actors such as the World Bank and the International Monetary Fund upon EU policy. It also considers contributing factors within the EU such as the enlargement of its membership and the resulting shifts in priorities. It is this analysis of internal and external factors affecting the decline of EU development policy that makes this study both innovative and unique. It brings together an impressive range of contributors from different disciplines resulting in a thorough and intelligent assessment of the debate. This study will appeal to advanced level undergraduates and academics of European politics in general, EU integration, development studies, and International Relations.